Pakistan's arms procurement and military build-up 1979-99 : in search of a policy - Siddiqa-Agha, Ayesha ([S.l.] : Sang-e-Meel Publications, 2003)
This book presents a fundamental departure in presenting an analysis of the internal dynamics of defense management and decision-making in Pakistan--a new nuclear weapon state. This is an in-depth study of Pakistan's security link with its arms suppliers and defense industrial capacity, and the influence of Pakistan's army on conventional and unconventional defense decisions. The analysis is backed with numerous case studies of defense decisions carried out from 1979-99.
Keywords: Armed Forces--Procurement; Defense industries; Military policy; Pakistan